2014
DOI: 10.1007/s40031-014-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of Real-Time Simulator and the Steps Involved for Implementation of a Model from MATLAB/SIMULINK to Real-Time

Abstract: Nowadays the researchers want to develop their model in real-time environment. Simulation tools have been widely used for the design and improvement of electrical systems since the mid twentieth century. The evolution of simulation tools has progressed in step with the evolution of computing technologies. In recent years, computing technologies have improved dramatically in performance and become widely available at a steadily decreasing cost. Consequently, simulation tools have also seen dramatic performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…OPAL-RT real-time simulation (RTS) technology is adopted in this study for electricity time-series simulations, as shown in Fig. 3 [12]. In RTS environment, the Host side and Target sider are two major parts.…”
Section: Simulation Mechanismmentioning
confidence: 99%
“…OPAL-RT real-time simulation (RTS) technology is adopted in this study for electricity time-series simulations, as shown in Fig. 3 [12]. In RTS environment, the Host side and Target sider are two major parts.…”
Section: Simulation Mechanismmentioning
confidence: 99%
“…For stability, the switching vector is obtained [17,26]: S(x) < 0, thereby constraining the effect of the external disturbance. However, the high frequency switching plane increases non linearity of the observer, leading to chattering.…”
Section: Structure Of Sliding Mode Luenberger State Observermentioning
confidence: 99%
“…For stability, the switching vector is obtained [17,26]: increases non linearity of the observer, leading to chattering. Therefore, to eliminate the effect of this unwanted phenomenon, a saturation function having boundary layer of width (Φ) is used by replacing sign(S) with sat(S/Φ) and is given by [17]:…”
Section: Structure Of Sliding Mode Luenberger State Observermentioning
confidence: 99%